2020
DOI: 10.3389/fpsyt.2020.585893
|View full text |Cite
|
Sign up to set email alerts
|

A New Hypothesis on Anxiety, Sleep Insufficiency, and Viral Infections; Reciprocal Links to Consider in Today's “World vs. COVID-19” Endeavors

Abstract: In today's ever-growing concerns about the coronavirus disease (COVID-19) pandemic, many experience sleep insufficiencies, such as difficulty falling or staying asleep, sleep-related behavioral symptoms, and out-of-phase circadian rhythmicity despite the lack of history of earlier such symptoms. Meanwhile, the disruption in sleep bioparameters is experienced more in people with a history of sleep disorders. The behavioral sleep disorders in the current situations are prevalent given the today's amount of anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 88 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…The results of the present work on sleep and the fear to be infected, ill, or fear of dying are also relevant in the context of a recent review work that warns about the impact of the triad sleep insufficiency, anxiety, and psychosocial stress hampering immunity against viral infections and increasing the individual susceptibility to COVID-19 ( 42 ). According to these authors, the state-of-art of sleep, anxiety, and COVID-19 is still based on former research.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results of the present work on sleep and the fear to be infected, ill, or fear of dying are also relevant in the context of a recent review work that warns about the impact of the triad sleep insufficiency, anxiety, and psychosocial stress hampering immunity against viral infections and increasing the individual susceptibility to COVID-19 ( 42 ). According to these authors, the state-of-art of sleep, anxiety, and COVID-19 is still based on former research.…”
Section: Discussionmentioning
confidence: 88%
“…Due to the emerging, and rapidly evolving situation of the COVID-19 pandemic, there is a strong need for further investigations as the virus seems meant to stay. Stress management measures, including addressing sleep-related disorders and sleep hygiene, are proposed to harness immune response and reduce viral infections' susceptibility ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a bidirectional connection between sleep and viral infections [ 72 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ] and growing evidence suggest that also the link between SARS-CoV-2 infection and sleep might be two-way as resumed in a recent review [ 88 ]. Several studies have recently highlighted the consistent role of SARS-CoV-2 infection on sleep characteristics, chronic fatigue, anxiety and depressive symptoms in caregivers, healthcare personnel, subjects affected by chronic diseases and healthy people due to extended lockdown [ 89 , 90 , 91 ]. A meta-analysis by Salari et al summarizing the prevalence of anxiety, stress and depressive symptoms in the general population during pandemic reported prevalence rates of 31.9%, 29.6% and 33.7%, respectively [ 92 ].…”
Section: Sleep Deprivation Immune System and Viral Infectionsmentioning
confidence: 99%
“…Disrupted sleep and psychosocial stress cause anxiety which leads to dysregulated endocrino-immunological responses 30 . Increase in cortisol levels, steroid insensitivity, proinflammatory mediators and cytokine reaction and decrease in circulating neural growth factor and brain-derived neurotrophic factor are manifestations of this disruption.…”
Section: Sleep Hygiene and Immunitymentioning
confidence: 99%